Anatomy and Histologic of Intrinsic Aging Skin - Putri Laksmi Karim; Inda Astri Aryani; Nopriyati (HM Publisher, 2021)
Aging is an inevitable and dynamic biological process that is characterized by the progressive deterioration of body systems and declines in physiological reserve capacity. Aging skin has distinct two types: intrinsic and extrinsic. Intrinsic changes reduce collagen production, blood flow, amount of skin lipid, and loss of rete ridges. Intrinsic aging or chronological aging is cannot be restored to the skin with characterized by sagging skin and some expression of excess wrinkling lines. Intrinsic aging changes in thickness and characteristics of the epidermis, dermis, and hypodermis. Histologically, epidermis thinner by leveling off the dermo-epidermal junction. In the dermis, collagen fibers become thicker and irregular than younger skin, reducing the elasticity of the skin, while hypodermis reduces lipid volume.